2013
DOI: 10.1093/eurheartj/eht176
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of prolonged PR interval in the general population

Abstract: AimsProlonged PR interval, or first degree AV block, has been traditionally regarded as a benign electrocardiographic finding in healthy individuals, until recent studies have suggested that it may be associated with increased mortality and morbidity. The aim of this study was to further elucidate clinical and prognostic importance of prolonged PR interval in a large middleaged population with a long follow-up. Methods and resultsWe evaluated 12-lead electrocardiograms of 10 785 individuals aged 30 -59 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 36 publications
10
87
3
1
Order By: Relevance
“…To the best of our knowledge, this is the first report to study the prognostic significance of prolonged PR interval in Asians. A significant association between the risk of mortality and prolonged PR interval was not found in the National Health and Nutrition Examination Survey (NHANES) [4], a Finnish population-based study [1], and our study. The only significant association reported arises from the Framingham study [3].…”
Section: Contents Lists Available At Sciencedirectcontrasting
confidence: 72%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first report to study the prognostic significance of prolonged PR interval in Asians. A significant association between the risk of mortality and prolonged PR interval was not found in the National Health and Nutrition Examination Survey (NHANES) [4], a Finnish population-based study [1], and our study. The only significant association reported arises from the Framingham study [3].…”
Section: Contents Lists Available At Sciencedirectcontrasting
confidence: 72%
“…The only significant association reported arises from the Framingham study [3]. The inconsistent results between the Framingham and Finnish populations might be because Framingham participants with prolonged PR interval were almost 10 years older than Finnish participants [1,3]. However, participants with prolonged PR interval in our study had a similar age and sex distribution to those in the Framingham study [3], although the mortality risk related to prolonged PR interval disappeared when confounders (age and sex) were considered.…”
Section: Contents Lists Available At Sciencedirectcontrasting
confidence: 59%
See 1 more Smart Citation
“…Although the prevalence of PR prolongation is relatively rare among the younger population (1% among those age <60 years) it becomes much more common after the age of ≥60 years, with prevalence rising to 6% 3. While it has been suggested that enhanced vagal tone underlies the aetiology of 1°HB in young people, organic heart disease is more prevalent in older subjects and may be linked to myocardial conduction system fibrosis and conduction abnormalities in these groups of patients 4. In patients who are incidentally found to have 1°HB, current expert advice suggests that 1°HB poses little risk, is not associated with significant symptoms and no specific treatment is required 5–7…”
Section: Introductionmentioning
confidence: 99%
“…3 Whether first-degree AV block in the general population is a nonrelevant finding or an indicator for increased cardiovascular risk is assessed controversially in the epidemiologic literature. 14,15 An increase in the QRS-width >120 ms during follow-up was associated with mortality. Changes in the depth distribution and/or extent of the Purkinje ventricular conduction network in patients with LVHT may lead to altered intraventricular conduction.…”
Section: Discussionmentioning
confidence: 99%